The Correlation Analysis of ISO 22000:2018 Food Safety Management System on the Family Companies Performance - Agus Purwanto; Khaerul Fahmi; Syahril Syahril; Irwansyah Irwansyah; Yoyok Cahyono; Arif Firmansyah (UJoST- Universal Journal of Science and Technology, 2022)
This study aims to determine the level of satisfaction of Family Business employees with the implementation of ISO 22000:2018 applied by the company, to determine the level of satisfaction of Family Business employees to the company's performance with the BSC perspective and to determine the effect of implementing ISO 22000:2018 on the achievement of company performance. This research is conducted by distributing questionnaires. Online Questionnaires were distributed to employees from several departments who represented and understood the condition of the company. Based on its nature, this research is descriptive, namely describing and explaining the effect of implementing ISO 22000:2018 on company performance. The respondents in this study were 444 Family Business employees from several departments who were considered to understand well the application of ISO 22000:2018. Sampling using purposive sampling technique, which is a sampling technique based on certain criteria with certain considerations. Based on the results of the analysis and discussion that has been carried out, the following conclusions: The level of employee satisfaction with the implementation of the ISO 22000:2018 food safety management system which consists of the application of the basic requirements program, the application of HACCP principles, the application of interactive communication and the application of the resource management system. The level of employee satisfaction with the achievement of company performance which consists of financial perspective, customer perspective, internal business process perspective and learning and growth perspective. The effect of implementing ISO 22000:2018 on the achievement of company performance is very significant and has a positive value, which means that there is a positive influence on company performance. The real effect can be seen in the number of Family Bisnis customers before implementing ISO 22000:2018 the number of customers, and after implementing ISO 22000:2018 there was a drastic increase in the number of customers. Implementation of the basic eligibility requirements program has the highest impact on company performance from financial performance, customer performance, internal business process performance and learning and growth performance